Hydrothermal synthesis and characterization of carbon nanospheres: a mechanistic insight - Bhagat, P. N.; Patil, K. R.; Bodas, Dhananjay S.; Paknikar, K. M. (RSC Advances, 2015)
Hydrothermally synthesized carbon nanospheres (CNS) follow a process of early nucleation followed by growth during synthesis. Here we report that growth occurs precisely after 5 min and prior to it nucleation occurs. The nucleation is a brief step in nanoparticle formation followed by growth of the nanoparticle depending on the reaction parameters.